2016
DOI: 10.1080/0269249x.2016.1193058
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of light quality and assemblage composition on diatom motility and accumulation rate

Abstract: 2016): Analysis of light quality and assemblage composition on diatom motility and accumulation rate, Diatom Research,The photosensitive nature of pennate diatom movement has long been observed, with cells being able to change the direction of their movement depending on the light conditions detected at the tips of the cells. However, much of this evidence is based on observations of cells in isolated, single-species culture, thus devoid of any information regarding inter-species interactions that might occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…The dependency of mating on blue light (and to a lower extent green light) in S. robusta and C. didymus 50 is in line with a general propensity of blue light to regulate various cellular processes in diatoms, such as cell cycle progression, phototaxis, vertical migration and production of metabolic compounds such as the pigment marennine 32 , 33 , 36 , 37 , 58 , 76 . The identification of functional red-light phytochromes in diatoms 19 and species-specific red light responses in motility and sinking 37 , 38 , 77 has recently challenged this perspective, suggesting that red light sensing plays a more important role in diatoms than was previously anticipated.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The dependency of mating on blue light (and to a lower extent green light) in S. robusta and C. didymus 50 is in line with a general propensity of blue light to regulate various cellular processes in diatoms, such as cell cycle progression, phototaxis, vertical migration and production of metabolic compounds such as the pigment marennine 32 , 33 , 36 , 37 , 58 , 76 . The identification of functional red-light phytochromes in diatoms 19 and species-specific red light responses in motility and sinking 37 , 38 , 77 has recently challenged this perspective, suggesting that red light sensing plays a more important role in diatoms than was previously anticipated.…”
Section: Discussionsupporting
confidence: 60%
“…Cells generally move upwards towards the sediment surface under moderate light intensities and migrate deeper into the sediment in darkness and under very high light intensities, resulting in synchronized rhythmic migration patterns over diurnal cycles 32 35 . Illumination experiments covering different wavelength ranges have shown that phototaxis and surface accumulation of motile diatoms is in most cases dependent on the presence of blue light 32 , 33 , 36 , 37 . Stauroneis phoenicenteron , on the other hand, is attracted to low intensity red light, suggesting that different benthic species employ different types of photoreceptors 24 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…These interspecies differences in frustule optical properties were claimed to additionally modulate the light availability inside the biofilm itself (Goessling et al, 2018a). Taken together with the fact that a species response to BL can be modulated by the presence of other species in its close surrounding (Cohn et al, 2016), it points out to the importance of the species consortium composition, which varies year around (this study, Haubois et al, 2005). Therefore, wavelengths, together with irradiance, would fine tune the differential rhythmic MPB migratory behavior and surface PAB accumulation versus the sediment light climate at the cell, species, and consortium (i.e., biofilm) levels.…”
Section: Influence Of the Light Spectrum On The Amount Of Pab Presentmentioning
confidence: 96%
“…Although green light generated a similar PAB accumulation than BL for the same intensity (40 µmol photons m −2 s −1 ), our experimental setup did not allow to test higher green light intensities to unambiguously conclude the responses to green light. It was previously demonstrated that green light (>510-520 nm) generally has a lower effect than BL (450 ± 20 nm) on phototactic directional cell movements (Nultsch, 1971;Cohn et al, 2004Cohn et al, , 2015Cohn et al, , 2016. Differently, red light of low or moderate intensity usually has no/little effect or negative effect on directional motility of diatoms and their accumulation, although this response is species-specific (Cohn and Weitzell, 1996;McLachlan et al, 2009;Cohn et al, 2015).…”
Section: Influence Of the Light Spectrum On The Amount Of Pab Presentmentioning
confidence: 99%
See 1 more Smart Citation